Efficient and automatic synthesis of TSPO PET ligand [18F]-GE-180 and its application in rheumatoid arthritis model. (June 2022) - Zhu, Xing-Xing; He, Yun-Lin; Xie, Ji-Kui; Wang, Kai-Xuan; Wang, Shi-Cun; Xie, Qiang
Abstract: Rheumatoid arthritis (RA) is a common autoimmune disease characterized by chronic synovial inflammation, which ultimately leads to joint deformity and dysfunction. [ 18 F]-GE-180 is a specific PET tracer of the 18 kDa translocator protein (TSPO), which is overexpressed on activated macrophages, and proposed as a biomarker of inflammation. Our study addresses the need to streamline the automatic synthesis of [ 18 F]-GE-180 to make it more accessible for routine production and widespread clinical evaluation and application. The nucleophilic radiofluorination was performed on an AllinOne synthesis module by SPE purification method, and the formulated [ 18 F]-GE-180 was obtained in non-decay corrected radiochemical yields of 69 ± 1.8% in 32 min. PET/CT imaging in animal model showed that [ 18 F]-GE-180 highly concentrated in joints from RA rats. This methodology facilitates efficient synthesis of [ 18 F]-GE-180 in a commercially available synthesis module and shows potential diagnosis performance in RA models. Highlights: A concise and efficient fully automatic synthesis of [ 18 F]-GE-180 by a commercially available synthesis module was proposed. The non-decay corrected radiochemical yield were 69 ± 1.8% with >95% radiochemical purity in 32 min. [ 18 F]-GE-180 is a potential PET tracer to evaluate rheumatoid arthritis and to determine disease activity. Facilitating the routine production and widespread use of [ 18 F]-GE-180 in clinical evaluation and application.